Policy Capacity and Governance
XXII, 445 p. 34 illus.
Keywords: This book provides unique insights into the role of policy capacity in policymaking and policy change, as it is being uncovered at the research frontier in contemporary policy studies. The book is structured into a series of sections on policy capacity in theory and practice, each focusing on a specific aspect of policy capacity and its influence on policy formulation, decision-making, implementation and evaluation. In addition to making a significant contribution to the body of literature on the theoretical approaches to researching the role of capacity in policymaking, it also provides practical examples of the application of these approaches through a variety of national and sectoral case studies. Including contributions from authors working in a wide variety of disciplines, the book demonstrates, across the various topics investigated, many commonalities and consistencies in relation to the study of policy capacity and policy-making. This work has interdisciplinary appeal and will engage scholars in fields ranging from geography to communications, health, social work and political science, amongst others with an interest in public policy.